2013
DOI: 10.1088/0031-9155/58/6/1983
|View full text |Cite
|
Sign up to set email alerts
|

A diffusion-compensated model for the analysis of DCE-MRI data: theory, simulations and experimental results

Abstract: Accurate quantification of pharmacokinetic parameters in dynamic contrast-enhanced (DCE) MRI may be affected by the passive diffusion of contrast agent (CA) within the tissue. By introducing an additional term into the standard Tofts-Kety (STK) model, we correct for the effects of CA diffusion. We first develop the theory describing a CA diffusion corrected STK model (DTK). The model is then tested in simulation with simple models of diffusion. The DTK model is also fit to 18 in vivo DCE-MRI acquisitions from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
59
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(63 citation statements)
references
References 29 publications
4
59
0
Order By: Relevance
“…In general the tumor vasculature, even in the well perfused region, is chaotic and poorly functional [40] and regions of hypoxia can co-exist with vasculature within the volume of an MRI voxel (390 μm × 390 μm × 1000 μm in this case). Similarly, agents that are non-specific for hypoxia also accumulate in hypoxic or necrotic regions by passive diffusion and demonstrate enhanced retention [41]. Indeed, GdDTPA (non-hypoxia specific clinical contrast agent) based pharmacokinetic parameters have been shown to correlate with hypoxia [42].…”
Section: Discussionmentioning
confidence: 99%
“…In general the tumor vasculature, even in the well perfused region, is chaotic and poorly functional [40] and regions of hypoxia can co-exist with vasculature within the volume of an MRI voxel (390 μm × 390 μm × 1000 μm in this case). Similarly, agents that are non-specific for hypoxia also accumulate in hypoxic or necrotic regions by passive diffusion and demonstrate enhanced retention [41]. Indeed, GdDTPA (non-hypoxia specific clinical contrast agent) based pharmacokinetic parameters have been shown to correlate with hypoxia [42].…”
Section: Discussionmentioning
confidence: 99%
“…Inter-voxel contrast agent diffusion has been the subject of simulation and experimental research that modifies the Tofts pharmacokinetic model [12,13]. Simulation of diffusion characteristics and contrast agent diffusion's associated effect on capillary permeability has also been the subject of research [14].…”
Section: Introductionmentioning
confidence: 99%
“…The diffusion‐corrected model improves on the Tofts model by including a diffusion term when calculating the changes in concentration as a function of time . In this study, because IAs are surrounded by the pial surface of the cerebral cortex, remote from white matter, we are able to reduce the computational complexity by approximating the diffusion rate ( D ) to be uniform in the extravascular space as follows: CDC(normalt)=ktranstrue0tekep(tτ)Cp(τ)dτ+vpCp(t)+true0ttrueNbold-italicDbold-italica2(bold-italicCbold-italicN(bold-italicτ)bold-italicveNbold-italicCbold-italici(bold-italicτ)bold-italicvei)dτ where C DC is the diffusion‐compensated tracer concentration, a is the in‐plane voxel length, D is the voxel‐specific diffusion constant, and C is the measured concentration.…”
Section: Methodsmentioning
confidence: 99%
“…Previous work by Fluckiger and Pellerin demonstrated that estimating kinetic parameters in the presence of passive contrast diffusion improved physiologic representation and reduced the likelihood of returning unphysical v e values. We apply a diffusion‐compensated Tofts model (DC‐Tofts) to analyze contrast kinetics at the surface of an IA wall.…”
Section: Introductionmentioning
confidence: 99%